The protective effect of fibroblast growth factor‐21 in alcoholic cardiomyopathy: a role in protecting cardiac mitochondrial function - Ferrer‐Curriu, Gemma; Guitart‐Mampel, Mariona; Rupérez, Celia; Zamora, Monica; Crispi, Fatima; Villarroya, Francesc; Fernández‐Solà, Joaquim; Garrabou, Gloria; Planavila, Anna (The Journal of pathology, 2021)
Alcoholic cardiomyopathy (ACM) resulting from chronic alcohol misuse is one of the main contributors leading to heart failure and cardiovascular mortality. Fibroblast growth factor 21 (FGF21) is a well‐established cardioprotective factor. We aimed to study the role of FGF21 in experimentally induced models and clinical affected patients with cardiac damage due to chronic alcohol consumption. We found that circulating FGF21 levels and cardiac FGF21 and β‐klotho protein levels were increased in subjects with chronic alcohol consumption. As an experimental model of ACM, we fed wild‐type and Fgf21 knockout (Fgf21−/−) mice with a 4% alcohol liquid diet for 4 and 12 weeks. FGF21 circulating levels and FGF21 expression in the myocardium were also increased in wild‐type mice after chronic alcohol intake. Fgf21−/− mice develop a higher degree of cardiac hypertrophy, fibrosis, and cardiac dysfunction after chronic alcohol consumption than wild‐type mice. Moreover, the myocardium of Fgf21−/− mice showed signs of metabolic deregulation, oxidative stress, and mitochondrial dysfunction after alcohol intake. Finally, human cardiac biopsies from patients with chronic alcohol consumption developing ACM presented a higher degree of oxidative stress which positively correlated with the FGF21 protein levels in the myocardium. We conclude that plasma levels and cardiac myocyte FGF21 expression were induced in response to chronic alcohol consumption. The lack of FGF21 aggravated cardiac damage produced by ACM, in association with enhanced mitochondrial and oxidative stress, thus pointing to FGF21 as a protective agent against development of alcohol‐induced cardiomyopathy. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.